Initiation of combined antiretroviral therapy confers suboptimal beneficial effects on neurovascular function in people with HIV - Singh, Meera V.; Uddin, Md Nasir; Singh, Vir B.; Peterson, Angelique N.; Murray, Kyle D.; Zhuang, Yuchuan; Tyrell, Alicia; Wang, Lu; Tivarus, Madalina E.; Zhong, Jianhui; Qiu, Xing; Schifitto, Giovanni (Frontiers in Neurology, 2023)
Introduction Due to advances in combined anti-retroviral treatment (cART), there is an increased burden of age-related cerebrovascular disease (CBVD), in people living with HIV (PWH). The underlying CNS injury can be assessed by measuring cerebral blood flow (CBF) and cerebrovascular reactivity (CVR). Methods 35 treatment-naïve PWH and 53 HIV negative controls (HC) were enrolled in this study. Study participants underwent T1-weighted anatomical, pseudo-continuous arterial spin labeling, and resting-state functional MRI to obtain measures of CBF and CVR prior to starting cART treatment and at two-time points (12 weeks and 2 years) post-cART initiation. Controls were scanned at the baseline and 2-year visits. We also measured plasma levels of microparticles of endothelial and glial origin and well-known endothelial inflammation markers, ICAM-1 and VCAM-1, to assess HIV-associated endothelial inflammation and the interaction of these peripheral markers with brain neurovascular function. Results HIV infection was found to be associated with reduced CVR and increased levels of endothelial and glial microparticles (MPs) prior to initiation of cART. Further, CVR correlated negatively with peripheral MP levels in PWH. Discussion Our results suggest that while cART treatment has a beneficial effect on the neurovascular function after initiation, these benefits are suboptimal over time.